Deriving a Proxy for Iron Limitation From Chlorophyll Fluorescence on Buoyancy Gliders - Ryan-Keogh, Thomas J.; Thomalla, Sandy J. (Frontiers in Marine Science, 2020)
Chlorophyll fluorescence, primarily used to derive phytoplankton biomass, has long been an underutilized source of information on phytoplankton physiology. Diel fluctuations in chlorophyll fluorescence are affected by both photosynthetic efficiency and non-photochemical quenching (NPQ), where NPQ is a decrease in fluorescence through the dissipation of excess energy as heat. NPQ variability is linked to iron and light availability, and has the potential to provide important diagnostic information on phytoplankton physiology. Here we establish a relationship between NPQsv (Stern-Volmer NPQ) and indices of iron limitation from nutrient addition experiments in the sub-Antarctic zone (SAZ) of the Atlantic Southern Ocean, through the derivation of NPQmax (the maximum NPQsv value) and αNPQ (the light limited slope of NPQsv). Significant differences were found for both Fv/Fm and αNPQ for iron versus control treatments, with no significant differences for NPQmax. Similar results from CTDs indicated that changes in NPQ were driven by increasing light availability from late July to December, but by both iron and light from January to February. We propose here that variability in αNPQ, which has removed the effect of light availability, can potentially be used as a proxy for iron limitation (as shown here for the Atlantic SAZ), with higher values being associated with greater iron stress. This approach was transferred to data from a buoyancy glider deployment at the same location by utilising the degree of fluorescence quenching as a proxy for NPQGlider, which was plotted against in situ light to determine αNPQ. Seasonal increases in αNPQ are consistent with increased light availability, shoaling of the mixed layer depth (MLD) and anticipated seasonal iron limitation. The transition from winter to summer, when positive net heat flux dominates stratification, was coincident with a 24% increase in αNPQ variability and a switch in the dominant driver from incident PAR to MLD. The dominant scales of αNPQ variability are consistent with fine scale variability in MLD and a significant positive relationship was observed between these two at a ~10 day window. The results emphasise the important role of fine scale dynamics in driving iron supply, particularly in summer when this micronutrient is limiting.